A New Preoperative Upright Design for Dermatochalasis Correction. Issue 6 (September 2021) - Chen, Ben; Woo, David Meng-da; Liu, Jia; Zhu, Xiuying; Lin, Yanyan; Ma, Yingjie; Chen, Xi
Abstract : Background: Conventional assessment of the height of upper eyelid skin excision in dermatochalasis correction is performed with patient's eyes closed in supine position. It is not able to consider the effects of gravity on the upper eyelid, thus may lead to asymmetric postoperative appearance. The authors herein report a novel preoperative upright design (PUD) that can accurately determine the amount of skin excision with patients' eyes open in dermatochalasis correction. Methods: Patients with dermatochalasis underwent PUD during blepharoplasty were enrolled and were followed-up for 9 to 15 months. Results: A total of 116 patients (mean age 55.1 ± 6.1 years, range 46–78 years) successfully underwent the surgery. Using the PUD, the vertical height of skin excision was 8.2 ± 2.4 mm (6–19 mm), the preoperative margin fold distance was −0.5 ± 1.0 mm (−4 – 1 mm), which improved to 2.1 ± 0.6 mm (1–3 mm, P < 0.05) at the last follow-up visit. A total of 107 of 116 patients (92.2%) were judged as "good" (natural double eyelid folds with symmetric margin fold distance), 9 patients (7.8%) were judged as "fair" (natural double eyelid folds with the differences of margin fold distance between fellow eyelids within 2 mm), and no one was judged as "poor" (unsmooth double eyelid folds or the differences of margin fold distance between fellow eyelids is more than 2 mm). Conclusion: Preoperative upright design is a simple and effective method to accurately determine the amount of skin excision in blepharoplasty, and help to achieve symmetric double eyelids.